Consumers Attitude about Blog and Community Marketing Across India and Australia - Purva Kansal AND Praveen Tiwari (Abhigyan, 2012)
Increase in the popularity of social networking and blogging sites has attracted the interest of the marketers and communication strategists, who forever are searching for new means of advertising. Advertising on these sites in the developed economies has been very successful and has led to increased positive recall and word of mouth advertising. Companies motivated by their success are duplicating the same models across social networking sites targeting different cultures and countries. It is in this backdrop that the current study was undertaken, with the objective to examine, if marketing on sites such as social communities and blogs, is perceived similarly and positively by the consumers across cultures. Furthermore, was it advisable for ompanies to blindly duplicate the communication model across communities and networking sites or was adaptability suggested. To answer these question data was collected from 80 respondents in India and 90 in Australia, by hosting the questionnaire link on popular blogging sites and communities on networking sites. To test the hypothesis chi square and Mann whitney tests were used. The results of the study highlight that consumers perceive customized marketing advertisements positively on blogs/ communities. This perception was influenced by cultural and demographic variables. Results highlighted that traditional advertisements needed to more sensitive to all demographic variables across cultures but online advertisements could be standardized to some extent. Results indicated that Indian online advertisements needed to be more sensitive to age and gender while Australian advertisements needed to be more sensitive to Age and education. According to the study, the best way to advertise online and to get noticed is to place the advertisement on a blog or community directed towards the target groups’ interests, and to tailor the advertisement itself to the blog or community. This research paper highlights the role of Cross Cultural issues on Blog and community marketing and adds to growing base of marketing literature concerning Blogs and communities as alternate means of marketing communication.